Promoting the Performance of 2D Material Photodetectors by Dielectric Engineering. Issue 2 (21st December 2021) - Lu, Jianting; Deng, Zexiang; Ye, Qiaojue; Zheng, Zhaoqiang; Yao, Jiandong; Yang, Guowei
Abstract: Low light absorption and limited carrier lifetime are two limiting factors hampering the further breakthrough of the performance of 2D materials (2DMs)‐based photodetectors. This study proposes an ingenious dielectric engineering strategy toward boosting the photosensitivity. Periodic dielectric structures (PDSs), including SiO2 /h‐BN, SiO2 /Al2 O3, and SiO2 /SrTiO3 (STO), are exploited to couple with 2D photosensitive channels (denoted as PDS‐2DMs). The responsivity, external quantum efficiency, and detectivity of an optimized SiO2 /STO(300 nm) ‐WSe2 photodetector reach 89081 A W −1, 2.7 × 10 7 %, and 1.8 × 10 13 Jones, respectively. These performance metrics are orders of magnitude higher than a pristine WSe2 photodetector, enabling reliable sub‐1 pW weak light detection. Based on systematic characterizations and first‐principle calculations, such dramatic performance improvement is associated with the promoted direct bandgap transition, reduced exciton binding energy, and PDS‐induced periodic intramolecular built‐in electric field across the atomically thin channels, which efficiently separates the photoexcited electron–hole pairs. More inspiringly, this strategy is also successfully exploited to 2D WS2 photodetectors, demonstrating broad applicability. As a whole, this work promises an exceptional avenue to ameliorate 2DM photodetectors and opens up a new horizon "dielectric optoelectronics, " simultaneously highlighting the role of dielectric environment during analyzing the fundamentals of 2DM devices. Abstract : By coupling 2D photosensitive channels with periodic dielectric substrates, multiple homojunctions are formed across the atomically thin channels and the photosensitivity is boosted by several orders of magnitude without compromising the response rate. This study opens up a new horizon denoted as "dielectric optoelectronics, " simultaneously highlighting the effect of dielectric environment in analyzing the fundamentals of 2D materials.